Exploring the role of township economy on youth empowerment, employment and entrepreneurship - Mbinda, Zoleka (Graduate School of Business (GSB), 2025)
High youth unemployment, growing inequality and poverty are interrelated and have long been teething problems in South Africa. The youth who form the largest proportion of the population of South Africa are marginalized from participating in the economy in any significant way and this places them at the receiving end of these problems. For these youth, micro and small entrepreneurial ventures in the informal or township economy seem to be the only viable solution out of these problems. The objective of this study was to explore the extent to which the township economy fosters entrepreneurship among the youth. The study leverages on the case study of Galeshewe Township in the Northern Cape and undertook an in-depth face-to face interview with small business owners in the township. The study was a qualitative study that allowed the respondents to express and describe their perceptions of whether township economy contributed towards youth empowerment, employment, and entrepreneurship. From the data that was coll